2009
DOI: 10.1111/j.1551-2916.2009.03270.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Gas Sensing Properties of TiO2–ZnO Core‐Shell Nanofibers

Abstract: We fabricated TiO2–ZnO core‐shell nanofibers via a novel two‐step process. In the first step, the TiO2 core nanofibers were synthesized by electrospinning. Subsequently, the ZnO shell layers were grown in a controlled manner using atomic layer deposition. The methodology proposed in this work is expected to be one of most suitable methods for preparing various kinds of oxide core‐shell nanofibers or nanowires. We investigated the O2 sensing properties of the synthesized core‐shell nanofibers. Good sensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(59 citation statements)
references
References 25 publications
1
58
0
Order By: Relevance
“…Park et al made TiO 2 -ZnO core-shell fibers using a TiO 2 template and atomic layer deposition. The core-shell fibers showed good oxygen sensing capability [106]. Zhan et al generated hollow TiO 2 fibers using a coaxial spinneret and machine oil as the core fluid.…”
Section: Core Shell Fibersmentioning
confidence: 99%
“…Park et al made TiO 2 -ZnO core-shell fibers using a TiO 2 template and atomic layer deposition. The core-shell fibers showed good oxygen sensing capability [106]. Zhan et al generated hollow TiO 2 fibers using a coaxial spinneret and machine oil as the core fluid.…”
Section: Core Shell Fibersmentioning
confidence: 99%
“…Yusoff et al [22], Maa et al [36], J.Y. Park group [37], Zubir et al [38] and several studies in the field of graphene-based composites were conducted in the past decade [39][40][41][42][43][44]. Most of the previous researches have been focused on either graphene with one component and/or a single core of magnetic nanomaterials with a single shell [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Electrospinning is one of the several methods available for the synthesis of 1-D nanofibers. Recently, TiO 2 -and SnO 2 -based nanofibers were fabricated by electrospinning techniques and several studies focused on their potential applications in areas such as gas sensing, photoelectrochemical applications, solar cells, and photocatalytic activity [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…When these two materials are coupled, it is expected that the photogenerated electrons from TiO 2 will be transferred to SnO 2 [10]. Many investigations have found that when these two oxides are coupled by suitable preparation methods, one can optimize their gas sensing or tune other properties required for various applications [4,5,9,[11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%